Electronic Delocalization in Two and Three Dimensions: Differential Aggregation in Indium "Metalloid" Clusters. (11th October 2017) - Protchenko, Andrey V.; Urbano, Juan; Abdalla, Joseph A. B.; Campos, Jesús; Vidovic, Dragoslav; Schwarz, Andrew D.; Blake, Matthew P.; Mountford, Philip; Jones, Cameron; Aldridge, Simon
Abstract: Reduction of indium boryl precursors to give two‐ and three‐dimensional M−M bonded networks is influenced by the choice of supporting ligand. While the unprecedented nanoscale cluster [In68 (boryl)12 ] − (with an In12 @In44 @In12 (boryl)12 concentric structure), can be isolated from the potassium reduction of a bis(boryl)indium(III) chloride precursor, analogous reduction of the corresponding (benzamidinate)In III Br(boryl) system gives a near‐planar (and weakly aromatic) tetranuclear [In4 (boryl)4 ] 2− system.